Antifungal Studies of Complexes of Schiff Base Derived from Anthracene Carboxaldehyde-L-Tyrosine - Indira Devi, G.; Parameswaran, Geetha; S.S., Veena (Asian Journal of Chemistry, 2016)
Tyrosine is a potential chelating agent, because this forms stable and coloured complexes with various metal ions. Schiff bases derived from tyrosine and their metal complexes have wide application in biological science. Mn(II), Co(II), Ni(II) and Cu(II) complexes of the type ML2[H2O]2 were synthesized and have been screened for their antifungal behaviour against Phytophthora capsici, the casual organism of foot rot of black pepper (Piper nigrum L.). The results show that the antifungal behaviour increases with increase in concentration.